Analisis Analisis Peran Akuntansi Manajerial Dalam Mengelola Biaya Dan Mendukung Keputusan Bisnis - Leony A Maranata Sinaga; Niska Susanti Waruwu; Rama Rayani Purba; Rayun Angelika Rianti Silaban; Ulibasa Lasromaitona Sihombing; Hamonangan Siallagan (Departement of Mathematics Education, 2024)
This study investigates the role of management accounting in controlling operating costs and supporting business decision-making processes in organizations. The main focus of this research is to gain an in-depth understanding of how management accounting can contribute significantly to optimizing operational costs, preparing effective budgets, and encouraging good decision making. The background to this research is based on the recognition that in today's competitive and dynamic economic environment, the success of a company is highly dependent on the ability to manage costs effectively and make timely strategic decisions. Management accounting is considered an important tool to support these efforts by providing management with relevant financial information and detailed analysis. This research is included in the type of qualitative research. The methodology used in this research is a systematic and structured library research method. The data used comes from trusted sources such as professional journals, textbooks, and related industry publications. Data analysis was carried out using qualitative and quantitative techniques to provide a comprehensive understanding of the contribution of management accounting in cost control and managerial decision making. These findings clearly show that management accounting plays an important role in controlling company operational costs. Management accounting provides accurate and relevant information about costs associated with business activities, enabling companies to take strategic steps to optimize costs and plan budgets more effectively. Additionally, business accounting helps businesses improve operational efficiency and achieve set financial goals by facilitating appropriate and timely decision making.